Comportamento de variáveis cardíacas em animais expostos à fumaça de cigarro - De Paiva, Sergio Alberto Rupp [UNESP] (2003)
Objective - To assess the behavior of cardiac variables in animals exposed to cigarette smoke. Methods - Two groups of Wistar rats were studied as follows: control group (C), comprising 28 animals; and smoking group (S), comprising 23 animals exposed to cigarette smoke for 30 days. Left ventricular cardiac function was assessed in vivo with transthoracic echocardiography, and myocardial performance was analyzed in vitro in preparations of isolated left ventricular papillary muscle. The cardiac muscle was assessed in isometric contractions with an extracellular calcium concentration of 2.5 mmol/L. Results - No statistical difference was observed in the values of the body variables of the rats and in the mechanical data obtained from the papillary muscle between the control and smoking groups. The values of left ventricular systolic diameter were significantly greater in the smoking animals than in the control animals (C=3.39 ± 0.4 mm and S=3.71 ± 0.51 mm, P=0.02). A significant reduction was observed in systolic shortening fraction (C=56.7 ± 4.2% and S=53.5 ± 5.3%, P=0.02) and in ejection fraction (C= 0.92 ± 0.02 and S=0.89 ± 0.04, P=0.01). Conclusion - The rats exposed to cigarette smoke had a reduction in left ventricular systolicfunction, although their myocardial function was preserved.